Functional and Predictive Structural Characterization of WRINKLED2, A Unique Oil Biosynthesis Regulator in Avocado - Behera, Jyoti R.; Rahman, Md. Mahbubur; Bhatia, Shina; Shockey, Jay; Kilaru, Aruna (Frontiers in Plant Science, 2021)
WRINKLED1 (WRI1), a member of the APETALA2 (AP2) class of transcription factors regulates fatty acid biosynthesis and triacylglycerol (TAG) accumulation in plants. Among the four known Arabidopsis WRI1 paralogs, only WRI2 was unable to complement and restore fatty acid content in wri1-1 mutant seeds. Avocado (Persea americana) mesocarp, which accumulates 60-70% dry weight oil content, showed high expression levels for orthologs of WRI2, along with WRI1 and WRI3, during fruit development. While the role of WRI1 as a master regulator of oil biosynthesis is well-established, the function of WRI1 paralogs is poorly understood. Comprehensive and comparative in silico analyses of WRI1 paralogs from avocado (a basal angiosperm) with higher angiosperms Arabidopsis (dicot), maize (monocot) revealed distinct features. Predictive structural analyses of the WRI orthologs from these three species revealed the presence of AP2 domains and other highly conserved features, such as intrinsically disordered regions associated with predicted PEST motifs and phosphorylation sites. Additionally, avocado WRI proteins also contained distinct features that were absent in the nonfunctional Arabidopsis ortholog AtWRI2. Through transient expression assays, we demonstrated that both avocado WRI1 and WRI2 are functional and drive TAG accumulation in Nicotiana benthamiana leaves. We predict that the unique features and activities of ancestral PaWRI2 were likely lost in orthologous genes such as AtWRI2 during evolution and speciation, leading to at least partial loss of function in some higher eudicots. This study provides us with new targets to enhance oil biosynthesis in plants.